Career Plateau: Constructs, Consequences and Coping Strategies - Ismail, Maimunah (Eurojournals, 2008)
The objective of this article is to examine constructs of career plateau. It begins with the meaning of career plateau, theorizing career plateau that includes types of plateauing and typologies of employees from the perspective of performance and career progression as well as chaos theory, measurements and consequences of career plateau. The article highlights the potential use of structural career opportunities, intrinsic job rewards and recognition as coping strategies to mitigate the effects of a plateau.